Tarptautinė unifikacija ir valstybinė bibliografija - Janonis, Osvaldas (Knygotyra, 1997)
Every single bibliographic agency knows from its own experience that only nation-wide standards ensure the exchange of bibliographic data inside the country. The development of international co-operation requires the adoption of standards on the international level. The international unification guarantees the compatibility of bibliographic data and the possibility of universal access to it. The article deals with the adaptation of international bibliographic standards to Lithuanian needs. Essential for Universal Bibliographic Control are the International Standards for Bibliographic Description (ISBD) and machine-readable formats—UNIMARC, international systems of standard numbering of publications (ISSN, ISBN, ISMN, ISRC, ISRN). New significance is acquired by the standards for authority data. The experience of the bibliographic agencies in foreign countries is characterized in the article. The author describes the situation of incorporating the international standards into the work of the bibliographic services, especially the National Bibliographic Agency (the Centre of Bibliography and Book Science). This Agency is responsible for translating the international standards, disseminating information about them, and monitoring the situation of their implementation. At present, Lithuania has a real possibility to join the international information system. In the conditions of the market economy, the main requirement is to prepare competitive bibliographic information corresponding to the standards and rules of the global bibliographic network.